Children in Tourism: a fresh perspective ? - Fiorella Dallari; Alessia Mariotti (Via@)
Tourism for children and adolescents is a neglected topic in tourism research, despite the importance of a child’s life trajectory up to the age of 17/18 in terms of the psychological and social impact it has on their formation of subjectivity. This paper aims to shed light on the topic, starting with an analysis of the scientific literature on childhood, including the thoughts of this cohort, which, as a review of the leading publications shows, has been neglected in the literature. There are various critical issues to consider, beginning with the way the age groups are classified ; they must be divided into childhood and adolescence to reflect minors’ cognitive ability and level of perception and interpretation. The existing literature is based on indirect information, collected from the family responsible for the minor. Using major, long-standing tourist destinations as case studies can reveal the marked importance of this age group, which has been neglected compared to the various adult and senior citizen tourist target groups and for whom innovative tourism options have not been provided. The case study presented focuses on the Riviera Romagnola, the largest Italian seaside tourist destination, responsible for Emilia-Romagna’s place in the top five European regions for hotel accommodation. It was a major coastal tourist destination for children between the two wars, welcoming an estimated 400,000 visitors in 1935 ; in recent years, public bodies, hotelier associations and private associations in the area have directed renewed energy towards this target group, due to growing awareness of new sustainable lifestyles. A survey in the Province of Rimini showed that tourists aged 17 and under still represent a very large target group (accounting for 640,000 visitors in 2013, equivalent to 1/5 of the total) and therefore a strategically important one ; new forms of holiday aimed at this group are now emerging, and innovative practices are being tested. Indeed, the authors highlight how this region, historically shaped by mass tourism, is being strengthened through new cultural projects and products aimed at children, involving best practices related to intangible and intergenerational heritage, as part of a vision of social and cultural sustainability.